Velázquez’s Democritus: Global Disillusion and the Critical Hermeneutics of a Smile - Berzal de Dios, Javier (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2016)
Velázquez’s Democritus (ca. 1630) presents a unique encounter: not only are there few depictions in which the Greek philosopher appears with a sphere that shows an actual map, but Velázquez used a court jester as a model for Democritus, thus placing the philosopher within a courtly space. When we study the painting in relation to the literary interests of the Spanish Golden Age and its socio-political circumstances, we can see the figure of Democritus as far from just another instantiation of a conventional trope. The philosopher’s smile and his crepuscular globe entrap the viewer in a semiotic game with pedagogical and ethical goals. While the scholarship on the painting has dwelt extensively on the identification of the figure, this essay moves beyond the superficial aspects of subject identity in order to explore how the painting articulates and requests a profoundly philosophical engagement. I thus examine Democritus in relation to contemporary literary and philosophical themes, many of which were present in Velázquez’s own personal library: the period’s understanding of the philosopher, cartographic spheres, and treatises on laughter. Considered in this manner, Velázquez’s figure is not responding to the folly of humanity in general, as is commonly the case in representations of the philosopher, but is rather presented through a courtly prism in which conquest, geography, and politics are inescapably interrelated. Velázquez’s Democritus emphasizes the philosophical and moral qualities of a learned and decorous laughter, which performs a critical and ethical role framed by Spain’s political difficulties.